Performance Comparison on Water Demand Methods Applied at Pengkalan Gawi, Kenyir Lake, Malaysia - Azlan N.N.I.B.M.; Norhisham S.; Malek M.A.; Shkuri N.S.M.; Zolkepli M.; Ean L.W.; Mohamad A.M. (Springer Science and Business Media Deutschland GmbH, 2023)
Lakes; Statistics; Water management; Water supply; Component analysis; Mean absolute deviations; Means square errors; Micro-component analyse; Microcomponent; National water service commission (SPAN) guideline; Performance; Performance accuracy; Water demand; Water service; Mean square error